Development of an empirical force field and molecular dynamics simulation of N,N'-dialkylimidazolium ionic liquids - Musanur Abrar, Siraj (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2004